Serotype distribution and prevalence of resistance to benzylpenicillin in three representative populations of Streptococcus pneumoniae isolates from the coast of Kenya. - Scott, J; Hall, A; Hannington, A; Edwards, R; Mwarumba, S; Lowe, B; Griffiths, D; Crook, D; Marsh, K (1998)
As surveillance data from sub-Saharan Africa are few, three representative populations of Streptococcus pneumoniae isolates were examined in Kenya for serotype distribution and Etest minimum inhibitory concentrations (MICs) of benzylpenicillin: (1) 75 lung aspirate or blood culture isolates from 301 consecutive adult patients with pneumonia, (2) 112 invasive isolates from continuous pediatric inpatient surveillance over 4 years, and (3) 97 nasopharyngeal isolates from systematically selected sick children. The proportions with benzylpenicillin MICs of > or = 0.1 microgram/mL were 0.27, 0.29, and 0.47, respectively. Vaccine-related serotypes accounted for 96% of invasive isolates from children and 90% of those from human immunodeficiency virus (HIV)-seropositive adults. Serotype 1 accounted for 44% of pneumococci from HIV-seronegative patients but only 5% of those from HIV-seropositive patients (P = .0002). Of serotype 1 isolates, 98% were susceptible to benzylpenicillin, but serogroups 13, 14, 19, and 23 were strongly associated with an MIC of > or = 0.1 microgram/mL.